Sex-specific cardiometabolic responses to chronic stress and the impact of prefrontal-medullary regulation - Dearing, Carley, author; Myers, Brent, advisor; Smith, Bret, committee member; Fails, Anna, committee member; Hoke, Kim, committee member (Colorado State University. Libraries, 2024)
Globally, cardiovascular and metabolic disease are leading causes of death and years lived with disability. Chronic stress is an etiologic factor in both diseases and biologic sex plays an important role in the progression and prognosis of each. However, the neurobiological basis of how chronic stress exposure intersects with sex, cardiovascular, and metabolic function to impact systemic physiology is poorly understood. Prior studies from our group indicate that, in rats, the prefrontal infralimbic cortex (IL)-rostral ventrolateral medulla (RVLM) circuit inhibits sympathetic and endocrine responses to stress. Therefore, we aimed to address the overarching hypothesis that the IL-RVLM circuit is necessary for homeostatic function and mitigation of deleterious changes to metabolic, cardiac, and microvascular function following chronic stress. To this end, an intersectional genetic approach was used to induce Cre-dependent expression of tetanus toxin light chain and inhibit neurotransmitter release from RVLM-projecting IL neurons in male and female rats. Rats were then exposed to 2 weeks of chronic variable stress (CVS). Metabolic function was assessed with a fasted glucose tolerance test. Cardiovascular function was examined with echocardiography and non-invasive hemodynamics. Additionally, microvascular function was quantified via ex-vivo resistance arteriole pressure myography. Our results indicate that glucose tolerance, left ventricular structure, and vascular function are all impacted in a sex-dependent manner. Following chronic stress, circuit-intact females show glucodysregulation characterized by decreased glucose clearance, elevated corticosterone, and insulin insensitivity. Regardless of stress, circuit inhibition in females also impaired glucoregulation but was characterized by elevated glucagon with no compensatory insulin response. Circuit inhibition also increased relative heart size, increased endothelial-dependent vasodilation at both normotensive and hypertensive pressures, and increased myogenic tone and diastolic wall strain. These changes indicate that chronic stress in females leads to broad endocrine-autonomic dysregulation of glucose homeostasis and microvascular function that is exacerbated by IL-RVLM inhibition. While chronic stress in males resulted in an adaptive metabolic response and no changes in normotensive vasodilation, circuit inhibition in chronically-stressed males lead to glucodysregulation and increased endothelial-dependent vasodilation at hypertensive pressures. Additionally, these animals had reduced ventricular wall thickness in diastole. Broadly, these results support the hypothesis that the IL-RVLM circuit is necessary for appropriate glucose homeostasis and vascular function and that circuit inhibition and chronic stress lead to sex-specific responses that may differentially impact the progression of cardiovascular and metabolic disease.
Keywords: cardiovascular; metabolic; autonomic; prefrontal-medullary; chronic stress